TiO2 anti-reflection composite structure and method for manufacturing the same

CN118151268BActive Publication Date: 2026-10-27INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410217052.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-28
Publication Date
2026-10-27
Estimated Expiration
2044-02-28

AI Technical Summary

Technical Problem

现阶段人们发展的蛾眼抗反射结构的加工技术步骤非常繁琐,在可见光波段内并不能很好地调控等效折射率梯度,基于透明介质的相关结构的加工技术也非常匮乏

Benefits of technology

[0037]本发明的TiO2抗反射复合结构具有优异的抗反射性能。本发明的方法简单且不需要使用较为复杂的套刻技术就可以使得图形结构的线宽(即,图形的横向距离)和周期均连续可控,可以实现任意的折射率梯度。此外,本发明的方法可以对图形结构的具体图案(包括图形结构涉及的角度和尺寸)实现连续可调。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118151268B_ABST
    Figure CN118151268B_ABST
Patent Text Reader

Abstract

The present application provides a TiO2 anti-reflection composite structure, which comprises a substrate layer and a structure layer located above the substrate layer; wherein the structure layer has a pattern structure, a longitudinal section of the pattern structure comprises a first part in the shape of a triangle and a second part in the shape of a rectangle, and the first part and the second part are integrally formed. The present application also provides a method for preparing the TiO2 anti-reflection composite structure. The TiO2 anti-reflection composite structure has excellent anti-reflection performance. The method is simple and can make the line width and period of the pattern structure continuously controllable without using a relatively complex overlay technology, and can realize an arbitrary refractive index gradient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of micro-nano fabrication and optics. Specifically, this invention relates to a TiO2 anti-reflection composite structure and its preparation method. Background Technology

[0002] Because of the difference in optical refractive index between media, light beams reflecting off the interface between two media can have a very detrimental effect on some optoelectronic devices. For example, light reflection from the surface of a liquid crystal display (LCD) degrades image quality, light emission from the surface of a solar cell reduces its absorption rate of sunlight, and the detection efficiency of light-emitting diodes (LEDs) and photodetectors is reduced due to interface light reflection. In the military field, light reflection from the surface of aircraft can also reveal targets. Therefore, reducing optical reflection at interfaces is a necessary technology in many fields.

[0003] Scientists have discovered that the light reflectivity of moth eyes is almost zero, inspiring the development of anti-reflective micro / nano optical structures. Moth-eye anti-reflective structures are essentially structures with a highly gradient change in refractive index. Their working principle can be explained by the equivalent refractive index theory: introducing a subwavelength micron-sized structure with a slowly changing equivalent refractive index at the air-object interface will result in a reflectivity far lower than that of an interface with abrupt refractive index changes. The anti-reflective efficiency and operating bandwidth of moth-eye anti-reflective structures are primarily determined by the tunability of the equivalent refractive index gradient. Simultaneously, the anti-reflective structure itself must not absorb light beams. Currently, the fabrication techniques for moth-eye anti-reflective structures are extremely complex, and the equivalent refractive index gradient cannot be well controlled within the visible light band. Furthermore, fabrication techniques for structures based on transparent media are also very limited.

[0004] Traditional etching techniques for micro / nano optical structures typically only etch vertically smooth structures, making it difficult to controllably etch structures with gradient changes in the vertical direction unless more complex overlay techniques and focused ion beam etching are used. Inductively coupled plasma etching (ICP-E) is a commonly used and simple method for fabricating micro / nano optical structures. Developing an ICP-E technique to fabricate "moth-eye" anti-reflective micro / nano optical structures would greatly advance the field.

[0005] Therefore, there is an urgent need for a method that is simple to prepare and produces patterned structures with excellent anti-reflective properties. Summary of the Invention

[0006] The purpose of this invention is to provide a TiO2 anti-reflection composite structure with excellent anti-reflection properties.

[0007] Another object of the present invention is to provide a method for preparing the TiO2 antireflective composite structure with excellent antireflective properties. This method is simple and does not require complex overlay techniques, allowing for continuous control over the linewidth (i.e., the lateral distance of the pattern) and period of the patterned structure, thus enabling arbitrary refractive index gradients. Furthermore, this method allows for continuous adjustment of the specific pattern of the patterned structure (including the angles and dimensions involved in the patterned structure).

[0008] The above-mentioned objective of the present invention is achieved through the following technical solution.

[0009] On one hand, the present invention provides a TiO2 anti-reflection composite structure, which includes a substrate layer and a structural layer located on the substrate layer; wherein,

[0010] The structural layer has a graphic structure, and the longitudinal section of the graphic structure includes a first part in the shape of a triangle and a second part in the shape of a rectangle, and the first part and the second part are integrally formed.

[0011] The inventors of this application unexpectedly discovered that when the graphic structure is designed such that the longitudinal section includes a first part in the shape of a triangle and a second part in the shape of a rectangle, the TiO2 anti-reflection composite structure of the present invention can possess an excellent refractive index gradient.

[0012] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the patterned structure includes multiple identical or different patterns.

[0013] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the pattern structure includes multiple patterns arranged periodically or non-periodically.

[0014] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the substrate is selected from one or more of silicon wafers, quartz and sapphire.

[0015] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the spacing between adjacent patterns of the patterned structure is greater than or equal to 10 nm, more preferably 10 nm-800 nm.

[0016] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the apex angle of the triangle is 30°-45°.

[0017] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the height of the triangle is 200nm-450nm.

[0018] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the triangle is an isosceles triangle.

[0019] Preferably, in the TiO2 antireflective composite structure of the present invention, the height of the second part is 100nm-500nm. The height of the second part refers to the length of the longitudinal side of the rectangle.

[0020] Preferably, in the TiO2 anti-reflection composite structure of the present invention, the period of the patterned structure is 300nm-1000nm.

[0021] Secondly, the present invention provides a method for preparing the TiO2 antireflective composite structure of the present invention, which includes the following steps:

[0022] (1) A TiO2 layer and a mask layer are deposited sequentially on the cleaned substrate;

[0023] (2) A photoresist layer is formed on the mask layer, and the photoresist layer is exposed, developed and fixed in sequence to form a patterned photoresist layer.

[0024] (3) Etch the structure obtained in step (2) to pattern the mask layer and obtain a patterned mask layer; then remove the residual photoresist layer.

[0025] (4) The structure obtained in step (3) is etched using inductively coupled plasma etching technology to pattern the TiO2 layer and obtain a structural layer with a patterned structure; then the remaining mask layer is removed to obtain a TiO2 anti-reflection composite structure including a substrate layer and a structural layer located on the substrate layer.

[0026] The inductively coupled plasma etching technology uses a source power of 250-400W and a radio frequency power of 90-240W.

[0027] The inventors of this application unexpectedly discovered that by adjusting the source power and radio frequency power of inductively coupled plasma etching technology, the structural layer with patterned structure of the present invention can be directly prepared without additional overlay process.

[0028] Preferably, in the method of the present invention, the mask layer is composed of one or more materials selected from Cr, W and Mo.

[0029] In this invention, the patterns in the patterned photoresist layer and the patterned mask layer mentioned in steps (2) and (3) respectively can be any shape such as rectangle, circle, triangle, polygon, grating, or array. For example, Figure 1 The left image shows that the mask can be an array pattern. Figure 1 The right figure shows that the mask can be a grating pattern.

[0030] Preferably, in the method of the present invention, the photoresist is an electron beam photoresist or an ultraviolet photoresist.

[0031] Preferably, in the method of the present invention, the electron beam photoresist is 6200, PMMA, or Zep.

[0032] Preferably, in the method of the present invention, the electron beam resist is 6200, and the ultraviolet photoresist is AZ resist or SU8 resist.

[0033] In a specific embodiment of the present invention, the cleaning in step (1) can be organic solvent cleaning, physical cleaning achieved by reactive ion etching, or chemical cleaning achieved by chemical acid / alkali solution, etc.

[0034] In a specific embodiment of the present invention, the deposition step in step (1) can be a physical vapor deposition method such as magnetron sputtering or thermal evaporation deposition, or a chemical vapor deposition method such as plasma-enhanced chemical vapor deposition.

[0035] In a specific embodiment of the present invention, the mask etching method is an ion milling, reactive ion etching, or plasma etching method, or it can be a wet etching technique based on a metal etching solution.

[0036] The present invention has the following beneficial effects:

[0037] The TiO2 antireflective composite structure of this invention exhibits excellent antireflective properties. The method of this invention is simple and does not require complex overlay techniques to ensure continuous control over the linewidth (i.e., the lateral distance of the pattern) and period of the patterned structure, enabling arbitrary refractive index gradients. Furthermore, the method of this invention allows for continuous adjustment of the specific pattern of the patterned structure (including the angles and dimensions involved in the patterned structure).

[0038] The TiO2 anti-reflection composite structure provided by this invention offers a new approach to military stealth design and a new method for the design and fabrication of micro-nano optical devices. Attached Figure Description

[0039] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:

[0040] Figure 1 A planar schematic diagram of the mask pattern in a specific embodiment of the present invention is shown, wherein the left image is an array pattern and the right image is a grating pattern;

[0041] Figure 2 A schematic flowchart illustrating the processing method of the TiO2 anti-reflection composite structure in a specific embodiment of the present invention is shown;

[0042] Figure 3The SEM image of the TiO2 antireflection composite structure prepared in Example 1 of the present invention is shown.

[0043] Figure 4 The reflectivity relationship of the TiO2 antireflection composite structure prepared in Example 1 of the present invention is shown with a silicon wafer as the reference wafer;

[0044] Figure 5 The SEM images of the prepared TiO2 anti-reflection composite structure are shown as the radio frequency power varies with the inductively coupled plasma etching technique.

[0045] Figure 6 The diagram illustrates the changes in key parameters of the prepared TiO2 antireflection composite structure when the radio frequency power used in inductively coupled plasma etching (ICP-E) is varied. These parameters include the triangle height, the triangle angle, and the spacing between unit structures. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the invention.

[0047] To better understand the present invention, the invention will be described in detail below with reference to the accompanying drawings and embodiments.

[0048] According to one embodiment of the present invention, the pattern in the patterned photoresist layer and the patterned mask layer can be any shape such as rectangle, circle, triangle, polygon, grating, or array. For example, Figure 1 The left image shows that the mask can be an array pattern. Figure 1 The right figure shows that the mask can be a grating pattern.

[0049] like Figure 2 As shown, it details the processing principle of the TiO2 anti-reflection composite structure. Following the process indicated by the arrow, the substrate is first prepared and cleaned, then functional materials are deposited on the substrate, followed by the deposition of mask materials. Photoresist is then spin-coated onto the mask materials, and exposure, development, and mask opening (fixing) operations are performed. Next, the photoresist is removed, and after the photoresist is removed, the TiO2 anti-reflection composite structure is etched.

[0050] Example 1

[0051] The preparation of the TiO2 anti-reflection composite structure in this embodiment includes the following steps:

[0052] (1) An 800nm ​​TiO2 layer and a 60nm Cr mask layer were deposited sequentially on the cleaned silicon substrate using EBD.

[0053] (2) A 300nm photoresist layer was formed on the mask layer using 6200.13 photoresist, and the photoresist layer was sequentially exposed (at a dose of 260μC / cm). 2 The process involves developing and fixing to form a patterned photoresist layer; wherein the developer is 600-546 and the fixer is isopropanol.

[0054] (3) The structure obtained in step (2) is etched using an inductively coupled plasma etching machine to pattern the mask layer and obtain a mask layer with a grating pattern. The linewidth of the grating is 300nm and the period is 600nm. The process parameters during the etching process are: source power 300W, radio frequency power 120W, Cl2 flow rate 80sccm, and O2 flow rate 10sccm. Then, the residual photoresist layer is removed using RIE. The RIE parameters are: power 100W, cavity pressure 100mTorr, and O2 flow rate 100sccm.

[0055] (4) The structure obtained in step (3) is etched using inductively coupled plasma etching (ICP-E) to pattern the TiO2 layer, obtaining a structure layer with a patterned structure. Then, the remaining mask layer is removed to obtain a TiO2 anti-reflection composite structure including a substrate layer and a structure layer located on the substrate layer. The source power of the ICP-E is 300W, and the radio frequency power is 150W. The etching results are as follows: Figure 3 As shown, Figure 4 The reflectivity of the etched TiO2 antireflective composite structure was measured against a silicon wafer.

[0056] Figure 3 The SEM image of the TiO2 antireflective composite structure prepared in Example 1 of the present invention is shown. Figure 3 The diagram shows that the triangle is an isosceles triangle with a vertex angle of 32°; the spacing between adjacent graphics in the graphic structure is 339nm; the height of the triangle is 399nm; the height of the second part (rectangle) is 261nm; and the period of the graphic structure is 600nm.

[0057] Figure 4 Optical tests of the prepared TiO2 antireflective composite structure are shown, with a silicon wafer as the reference. Figure 4 The prepared TiO2 anti-reflection composite structure has a reflectivity of 10-20% that of the silicon wafer, indicating that it has a certain anti-reflection effect.

[0058] Example 2

[0059] Investigating the effect of radio frequency power on the parameters of the prepared TiO2 antireflection composite structure

[0060] The same preparation method as in Example 1 was used, except that the radio frequency power used in the inductively coupled plasma etching technique was changed (see details). Figure 5 The parameters for preparing the mask layer pattern are also specified. Specifically, the grating parameters are adjusted to a linewidth of 200 nm and a period of 300 nm.

[0061] Figure 5 The SEM images show the changes in the prepared TiO2 anti-reflection composite structure when the radio frequency power used in inductively coupled plasma etching (ICP-E) is varied.

[0062] Figure 6 The results show the changes in the main parameters of the prepared TiO2 antireflection composite structure when the radio frequency power used in inductively coupled plasma etching (ICP-C) is varied. These parameters include the height of the triangle, the angle of the triangle, and the spacing between the unit structures.

[0063] This embodiment demonstrates that the method of the present invention is simple and does not require complex overlay techniques to achieve continuous and controllable linewidth (i.e., lateral distance of the pattern) and period of the pattern structure, enabling arbitrary refractive index gradients. Furthermore, the method of the present invention allows for continuous adjustment of the specific pattern of the pattern structure (including the angles and dimensions involved in the pattern structure).

[0064] The basic principles of this application have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in this application are merely examples and not limitations, and should not be considered as essential features of each embodiment of this application. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the application to the necessity of employing the aforementioned specific details for implementation.

[0065] The block diagrams of devices, structures, methods, and systems involved in this application are merely illustrative examples and are not intended to require or imply that they must be connected, arranged, or configured in the manner shown in the block diagrams. As those skilled in the art will recognize, these devices, apparatuses, devices, and systems can be connected, arranged, and configured in any manner. Words such as “comprising,” “including,” “having,” etc., are open-ended terms meaning “including but not limited to,” and are used interchangeably with them. The terms “or” and “and” as used herein refer to the terms “and / or,” and are used interchangeably with them unless the context clearly indicates otherwise. The term “such as” as used herein refers to the phrase “such as but not limited to,” and is used interchangeably with it.

[0066] It should also be noted that in the apparatus, equipment, and methods of this application, the components or steps can be disassembled and / or recombined. These disassemblies and / or recombinations should be considered as equivalent solutions of this application.

[0067] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use this application. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein can be applied to other aspects without departing from the scope of this application. Therefore, this application is not intended to be limited to the aspects shown herein, but rather to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a TiO2 antireflective composite structure, comprising the following steps: (1) A TiO2 layer and a mask layer are deposited sequentially on the cleaned substrate; (2) A photoresist layer is formed on the mask layer, and the photoresist layer is exposed, developed and fixed in sequence to form a patterned photoresist layer; (3) Etch the structure obtained in step (2) to pattern the mask layer and obtain a patterned mask layer; Then remove the remaining photoresist layer; (4) The structure obtained in step (3) is etched using inductively coupled plasma etching technology to pattern the TiO2 layer and obtain a structural layer with a patterned structure. Then the remaining mask layer is removed to obtain a TiO2 anti-reflection composite structure including a substrate layer and a structural layer located on the substrate layer; The inductively coupled plasma etching technology uses a source power of 250-400W and a radio frequency power of 90-210W. The TiO2 anti-reflection composite structure includes a substrate layer and a structural layer located on the substrate layer; wherein... The structural layer has a graphic structure, and the longitudinal section of the graphic structure includes a first part in the shape of a triangle and a second part in the shape of a rectangle, and the first part and the second part are integrally formed; The spacing between adjacent patterns in the graphic structure is 10nm-800nm; The period of the pattern structure is 300nm-1000nm.

2. The method according to claim 1, wherein, The substrate is selected from one or more of silicon wafers, quartz and sapphire.

3. The method according to claim 1, wherein, The vertex angle of the triangle is 30°-45°.

4. The method according to claim 1, wherein, The height of the triangle is 200nm-450nm.

5. The method according to claim 1, wherein, The triangle is an isosceles triangle.

6. The method according to claim 1, wherein, The height of the second part is 100nm-500nm.

7. The method according to claim 1, wherein, The mask layer is composed of one or more materials selected from Cr, W and Mo.

8. The method according to claim 1, wherein, The photoresist is an electron beam photoresist or an ultraviolet photoresist.

9. The method according to claim 8, wherein, The electron beam photoresist is 6200, PMMA, or Zep.

10. The method according to claim 8, wherein, The electron beam photoresist is 6200, and the ultraviolet photoresist is AZ or SU8.

Citation Information

Patent Citations

  • Antireflective structure and antireflective molded body

    CN101377554A

  • Long laminated sub-wave reflection-reducing structure and preparation method thereof

    CN101726769A